2022
DOI: 10.3389/fneur.2022.836033
|View full text |Cite
|
Sign up to set email alerts
|

Different Clinicoradiological Characteristics of Posterior Reversible Encephalopathy Syndrome in Pediatric Oncology and Post-Bone Marrow Transplantation Cases: A Retrospective Study

Abstract: Posterior reversible encephalopathy syndrome (PRES) is receiving increasing recognition in pediatrics. However, comparisons between PRES in pediatric oncology and post-bone marrow transplantation (BMT) are lacking. Therefore, we aimed to describe the risk factors and clinical and radiological features of PRES and investigate the differences between PRES in pediatric oncology and post-BMT. The PRES data of 13 patients from our center were combined with those of 217 cases from the PubMed, Scopus, and Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In children with hemoglobinopathies, PRES has been reported in patients treated with calcineurin inhibitors (cyclosporin, sirolimus and tacrolimus) ( 4 , 6 , 19 , 20 ). In one series of children with SCD and thalassemia who underwent SCT from Rome (age range 2–17 years old), PRES was reported in 31 of 222 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children with hemoglobinopathies, PRES has been reported in patients treated with calcineurin inhibitors (cyclosporin, sirolimus and tacrolimus) ( 4 , 6 , 19 , 20 ). In one series of children with SCD and thalassemia who underwent SCT from Rome (age range 2–17 years old), PRES was reported in 31 of 222 cases.…”
Section: Discussionmentioning
confidence: 99%
“…PRES has been reported with several hematological disorders including thalassemia and sickle cell disease (SCD) ( 4–6 ). In SCD, most cases have been reported in children in close proximity to stem cell transplantation (SCT).…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al. studied the difference between PRES in pediatric oncology and post-HCT patients and found that oncology patients developed PRES at a younger age and were more likely to present with encephalopathy ( 70 ). Systemic HTN preceded PRES in 43.5% of patients, and this was more likely in post-HCT patients.…”
Section: Management Of Ckd In a Patient With Hctmentioning
confidence: 99%
“…The primary composite endpoint of 50% GFR decline and ESKD favored the intensive BP arm (HR: 0.65; 95% CI: 0.44-0.94) (69). Children with systemic HTN have a narrower range of autoregulation in cerebral blood flow and an increased risk of cerebrovascular dysfunction, making them more susceptible to posterior reversible encephalopathy syndrome (PRES) (70). PRES presents with an abrupt, acute rise in BP along with seizures, visual changes, encephalopathy, headache, and radiologic findings on brain magnetic resonance imaging (MRI) with focal reversible vasogenic edema (71).…”
Section: Complications Of Ckd: Hypertension and Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation